Microstructural evolution and compressive properties of nanocrystalline Ti–Fe alloy fabricated via cryomilling and spark plasma sintering - Lee, Hansung; Sharma, Ashutosh; Ahn, Byungmin (Journal of Materials Science, 2022)
Nanostructured Ti–Fe alloys were fabricated by cryomilling and spark plasma sintering (SPS). Cryomilling was performed for 8 h in a liquid N2 atmosphere, and densification of the alloyed mixture was performed at different SPS temperatures (800, 1000, and 1200 °C). The phase and structure of the Ti–Fe alloyed powder were studied by X-ray diffraction analysis. The morphologies of the cryomilled powders and SPS-treated compacts were investigated by scanning and transmission electron microscopic analyses. The results showed that alloying did not occur completely in the powder mixture after cryomilling and pure Ti and Fe phases were found. However, SPS treatment of cryomilled Ti–Fe powder resulted in a different phase evolution with temperature. Intermetallic compounds were formed in small amounts in the Fe-rich region; however, β-Ti phases were mostly present. The absorption energies of these alloys showed small changes from 460, 452, and 430 MJ/m3 when the SPS temperatures were 800, 1000, and 1200 °C, respectively. The compressive strength values of these Ti–Fe alloys improved with increasing SPS temperature owing to the diffusion of Fe in the Ti matrix, which promoted the dispersion hardening of these alloys.
Keywords: Alloyed powder; Compressive properties; Cryomilling; Densifications; Nanocrystallines; Nanostructured Ti; Scanning electrons; Sintering temperatures; Spark-plasma-sintering; TiFe alloys